2016
DOI: 10.7150/ijms.16267
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Myostatin Stimulates Regenerative Potential of Injured Antigravitational Soleus Muscle in Mice under Unloading Condition

Abstract: Effects of myostatin (MSTN)-suppression on the regeneration of injured skeletal muscle under unloading condition were investigated by using transgenic mice expressing a dominant-negative form of MSTN (MSTN-DN). Both MSTN-DN and wild-type (WT) mice were subjected to continuous hindlimb suspension (HS) for 6 weeks. Cardiotoxin (CTX) was injected into left soleus muscle under anesthesia 2 weeks after the initiation of HS. Then, the soleus muscles were excised following 6-week HS (4 weeks after CTX-injection). CTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Acute muscle injury was induced by injecting the gastrocnemius, soleus, and TA muscles with 10 μM CTX ( Naja mosambica ; Sigma, St. Louis MO, USA) in 150 μL of phosphate‐buffered saline (PBS). The contralateral limb was injected with 150 μL of PBS as a vehicle control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute muscle injury was induced by injecting the gastrocnemius, soleus, and TA muscles with 10 μM CTX ( Naja mosambica ; Sigma, St. Louis MO, USA) in 150 μL of phosphate‐buffered saline (PBS). The contralateral limb was injected with 150 μL of PBS as a vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were checked continually for vitality and responsiveness. After the functional evaluation, the right hindlimb gastrocnemius and soleus muscles were each injected with 100 μL of 10 μM CTX ( Naja mosambica ) to induce muscle damage as described earlier. An equal volume of PBS was injected into the contralateral leg as a vector control.…”
Section: Methodsmentioning
confidence: 99%
“…Myostatin maintains the quiescence of SCs, whereas its absence triggers activation of SCs. Deletion of myostatin gene favors muscle mass and may lead to muscle hypertrophy (Ohno et al, 2016). Moreover, myostatin blockade elicited an improvement in the regenerative potential of limb muscles of mice following cardiotoxin‐induced injury (Ohno et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CTX has been used to induce skeletal muscle injury in many mouse models ( Table 1 ) including that of diabetes, obesity, aging, exercise training, mechanical loading, and nutrition intervention, among others. Studies have shown that streptozocin and gene mutation-induced diabetes [ 20 , 21 , 22 , 23 ], high fat diet-induced obesity and ob/ob mice [ 22 , 24 , 25 ], cancer cachexia [ 26 ], aging [ 27 , 28 ], irradiation [ 29 ], elevated carbon dioxide (CO 2 ) level [ 30 ], and hindlimb suspension [ 31 , 32 ] lead to impaired regeneration, whereas exercise training [ 33 , 34 ], microcurrent electrical neuromuscular stimulation [ 35 ], microelement zinc [ 36 ], and overloading [ 37 , 38 ] improve the regeneration of CTX-induced damaged muscle. The accumulation of mitochondrial DNA alterations activates muscle regeneration in myofibers during aging, but leads to reduced muscle mass [ 39 ].…”
Section: Skeletal Muscle Regeneration In Different Mouse Models After...mentioning
confidence: 99%